Determination of antioxidants in pineapple waste / Anizah Mahmod - Mahmod, Anizah (Faculty of Applied Sciences, 2009)
The experiment was conducted to identify the antioxidants activities in the pineapple waste. Three sample were used which are leaves, crown and skin. Three methods were used which are 1,1-diphenyl-2-picrylhydrazyl (DPPH), Ferric Reducing Antioxidant Potential (FRAP) and Total Phenolic Content (TPC). UV-Visible Spectrophotometer was using in this analysis. Using ethanol, leaves show the greatest in the TPC compared to the skin and crown. Leaves shows 11.83mg/100g, followed by crown, 7.49mg/100g and skin, 1.90mg/100g. The results were expressed in Gallic Acid Equivalent (GAE). Leaves also showed the highest scavenging effect compared to the crown and skin. FRAP measures the ability of the extract to donate electron to Fe (III). The higher the FRAP value, the greater is the antioxidant activity. The highest value of FRAP was leaves followed by crown and skin. Crown and skin showed quite similar of ferric reducing potential.